A Study on Relationship Between Decision-making Behaviour and Myers-Briggs Type Indicator - Chen, Jelico (2007)
This paper investigates the relationship between a famous personality model, Myers Briggs Type Indicator (MBTI), and decision-making behavior. As Van Damme (1999) suggests that studying decision-making behavior from psychological perspective can bring out more realization about choice behavior. Also, psychological researches (Genovesio et al 2005; Wilson, Stevenson and Potts 2006) disclose that decision-making processes are really affected by brain activity, which is the other side of humansÃ¢ÂÂ psychological features. The facts motive the present research to take MBTI personality model as the instrument and further detect the relationship. The exploration about decision-making behavior is limited in four specific issues: tendency of taking risk, attitude to cooperation and degree of valuing humanity. The result shows that there is a weak link between decision-making behavior and MBTI.